Early Adverse Reactions to Snake Antivenom: Poison Center Data Analysis - Sriapha C. (2023)
Antivenom is an essential treatment for snake envenomation; however, early adverse reactions (EARs) are major limitations to its use. We performed a retrospective cross-sectional study using Ramathibodi Poison Center data (January 2016 to December 2017) to clarify the incidence and severity of EARs following different F(ab’)2 antivenoms. Among 1006 envenomed patients, 684 (68%) received antivenom therapy with a total of 1157 doses, mostly green pit viper antivenom. The overall EAR incidence and rate were 22. 5% (154/684) and 15% (173/1157), respectively. The EAR rate following each type of antivenom was >10%, except for Russell’s viper antivenom (2.9%); the severe reaction rate was 2.6% (30/1157). Malayan pit viper bites caused a high incidence of EARs (37.8%) and the highest EAR rate (22.3%). Fifty-two cases developed anaphylaxis. All EARs occurred within 2 h after treatment initiation. No deaths were attributed to EARs. The duration of administration was significantly different between doses of antivenom that induced EARs and those that did not. In conclusion, all types and every dose of antivenom should be infused for 30–60 min. Preparation of resuscitation equipment and continuous clinical observation are crucial for at least 2 h after administration, and prompt treatment should be provided when EARs occur.